School Britannia? Rhetorical and educational uses of 'British values' (UCL Press, 2018)
Schools in England are now required by law to 'actively promote British values' (DfE, 2014). This paper seeks to set this requirement within the context of a somewhat longer history of debates about values in Britain. It discusses the views of certain neoconservatives who claim that multiculturalism has eroded or even abolished British values. It then discusses the refocusing of the debate in relation to the rise of Islamist terrorism and examines some of the key rhetorical responses of leading UK politicians. The view that 'promoting British values' will strengthen identities and promote social cohesion is challenged. The concluding section of the paper develops an argument focused on liberal values, and stresses the importance in a pluralistic society of prioritizing certain values over others - notably rationality and autonomy - especially in education. Aspects of the work of Amartya Sen, John Rawls, Bernard Crick and Charles Bailey are discussed in this regard.